Justice for the dead - Singata, Silakhe (Stellenbosch Theological Journal, 2021)
The objective of this article is to reflect on the challenge issued by John D. Caputo, in his approach to the resurrection, to rewrite the history of the suffering with prayers and tears. In order to ground this reflection in the African context, the notion of remembering the dead in weak theology will be brought into conversation with the African traditional practice of venerating ancestors. This is all to approach an act of remembering the victims of the past which is different from historiography.